(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
:This article delves into the intricacies of financial risks inherent in pension funds, exploring their impact on retirement security and strategies for risk mitigation. Financial risks, including market risk, interest rate risk, inflation risk, longevity risk, and liquidity risk, pose significant challenges to the stability and sustainability of pension funds. Through comprehensive risk management methods such as risk identification, assessment, and mitigation, pension funds strive to enhance resilience and optimize risk-adjusted returns.